The ghosts of Trappist - Wagers, K. B. (Wagers, K. B. NeoG novel, 2023)
As Zuma's Ghost gears up for a final run at the Boarding Games, ensign Sapphi Zika and her crew are under attack by something out beyond the asteroid belt, which has been taking their ships, but no one is prepared for the truth that is revealed, shaking the foundations of everything they believe.